2018
DOI: 10.1186/s12903-018-0605-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and health-related quality of life in HIV patients

Abstract: BackgroundOral health care may improve the health-related quality of life (HRQoL) of HIV/AIDS patients. We aimed to evaluate oral health and HRQoL of HIV/AIDS patients using antiretroviral therapy.MethodsA cross-sectional study included 120 HIV-infected patients, aged ≥18 years, from February, 2016 to September, 2017. The 36-Item Short Form Health Survey (SF-36) was used to evaluate the HRQoL. We assessed dental caries status using the Decayed, Missing and Filled Teeth (DMFT) index. Information about demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
(39 reference statements)
3
22
1
Order By: Relevance
“…In the present research, similar to other studies [ 5 , 8 , 16 , 17 ], no significant difference was found between female and male individuals' OHRQoL. On contrary, in Tomar et al [ 15 ] study, women had worse OHRQoL than men.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present research, similar to other studies [ 5 , 8 , 16 , 17 ], no significant difference was found between female and male individuals' OHRQoL. On contrary, in Tomar et al [ 15 ] study, women had worse OHRQoL than men.…”
Section: Discussionsupporting
confidence: 89%
“…However, because of the modern therapeutic measures, the life expectancy of the patients infected with HIV has increased. Nevertheless, because of several health-related outcomes, which lead to chronic comorbidities, HRQoL in HIV-infected patients has been reported as poor [ 5 ]. In addition, many of the patients suffer from oral health problems and experience at least one oral disease during their illness [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the pooled DMFT index score was 23.48 (95% CI: 22.34, 24.62), which is higher than reported in other populations. For example, the DMFT index score was 2.37 in adolescent workers in Turkey, 56 6.38 in refugees in Germany, 57 12.4 in HIV‐infected patients in Brazil, 58 and 13.33 in older people in China 59…”
Section: Discussionmentioning
confidence: 99%
“…Adequate oral health care and the maintenance of a pleasant smile with esthetic restorations may improve the quality of life in HIV-positive patients [ 16 ]. However, due to progressive immunocompromise, it may be preferable to reduce the number of traumatic clinical procedures in patients diagnosed with HIV.…”
Section: Case Presentationmentioning
confidence: 99%